Evaluation of Graft Tensioning Effects in Anterior Cruciate Ligament Reconstruction between Hamstring and Bone–Patellar Tendon Bone Autografts - DeFroda, Steven F.; Karamchedu, Naga Padmini; Budacki, Ross; Wiley, Taylor; Fadale, Paul D.; Hulstyn, Michael J.; Shalvoy, Robert M.; Badger, Gary J.; Fleming, Braden C.; Owens, Brett D. (The Journal of Knee Surgery, 2020)
This article investigates the clinical, functional, and radiographic outcomes in anterior cruciate ligament (ACL) reconstruction patients over 7 years to determine the effects of initial graft tension on outcomes when using patellar tendon (bone–tendon–bone [BTB]) and hamstring tendon (HS) autografts. Ninety patients, reconstructed with BTB or HS, were randomized using two initial graft tension protocols: (1) normal anteroposterior (AP) laxity (“low-tension”; n = 46) and (2) AP laxity overconstrained by 2 mm (“high-tension”; n = 44). Seventy-two patients had data available at 7 years, with 9 excluded for graft failure. Outcomes included the Knee Injury and Osteoarthritis Outcome Score, Short-Form-36 (SF-36), and Tegner activity scale. Clinical outcomes included KT-1000S and International Knee Documentation Committee examination score; and functional outcomes included 1-leg hop distance and peak knee extensor torque. Imaging outcomes included medial joint space width, Osteoarthritis Research Society International radiographic score, and Whole-Organ Magnetic Resonance Score. There were significantly improved outcomes in the high-tension compared with the low-tension HS group for SF-36 subset scores for bodily pain (p = 0.012), social functioning (p = 0.004), and mental health (p = 0.014) 84 months postsurgery. No significant differences in any outcome were found within the BTB groups. Tegner activity scores were also significantly higher for the high-tension HS group compared with the low-tension (6.0 vs. 3.8, p = 0.016). Patients with HS autografts placed in high tension had better outcomes relative to low tension for Tegner activity score and SF-36 subset scores for bodily pain, social functioning, and mental health. For this reason, we recommend that graft fixation be performed with the knee at 30-degree flexion (“high-tension” condition) when reconstructing the ACL with HS autograft.
Keywords: ACL; graft selection; graft tensioning